Advocating Personal Learning Environment (PLE) in Scientific Writing: Is Digital Tool More Powerful? - Athi Fauzani Wisudawati (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
Personal learning environment (PLE) connects the formal and informal learning of the learners by utilizing both digital and non-digital tools. This concept is believed to be able to support the process of learning Scientific Writing because to construct an article is not enough relying on formal learning and a single tool provider. This paper reports the implementation as well as the tools used and impact of getting engaged in PLE for learning Scientific Writing. The research was conducted qualitatively in narrative inquiry analysis while the data was collected through observation, questionnaire and in-depth interview. The participant was a graduate student majoring English Education department having experienced making a scientific journal. The learner admitted that collaborating both digital and non-digital tools is very meaningful, however the use of digital tools apparently more efficient as supported by Reinders (2014) to support different aspects of the learning process. This study is beneficial for ELT classroom, specifically for academic writing class where Scientific Writing is one of mandatory subject being taught by the lecturer. The tools revealed in the finding can be references for EFL learners to be applied in constructing Scientific Writing.